Pengaruh Electronic Word of Mouth (E-WoM) terhadap Keputusan Pembelian Kamar di Fave Hotel Olo Padang - Rechia, Arixa Renda; Wulansari, Nidia (Lembaga Yasin AlSys, 2023)
The background of this research is because of the many positive and negative reviews written by guests about Fave Hotel Olo Padang via the internet. Testing how much influence electronic word of mouth has on the decision to purchase a room at the Fave Olo Hotel Padang is the aim of this study. There were 1093 respondents in this study, but only 204 samples using purposive sampling method. The questionnaire uses a Likert scale to collect this data information. To ensure its accuracy, the questionnaire has been tested for validity and normality. Simple regression analysis was used for hypothesis testing. SPSS 20.00 software was used to perform the analysis. The results are, (1) electronic word of mouth has a fairly good value, namely 41%, and (2) the decision to buy a room has a fairly good value, namely 30%. The calculated f value is 64,048 which concludes that Electronic Word of Mouth and purchasing decisions have a significant effect with a Sig value of 0.000 <0.05. Based on the R square value of 0.241, 24.1% electronic word of mouth influences purchase decisions while 75.9% is influenced by other factors.